Tatwīr al-Mawād at-Ta’līmiyah al-Maudū’iyah bi al-Lugah al-‘Arabiyah Li Țullāb Qism Ta’līm Mudarrisī al-Madrasah al-Ibtidā’iyah bi Ma’had al-Tanwīr al-islamī Bojonegoro - Nisa', Dwi Khoirotun (Journal of Language Intelligence and Culture, 2020)
The purpose of this research are: (1) knowledge of the process of developing thematic learning materials in the Arabic language for students of the elementary school teacher education department of the Islamic Institute of Religion Attanwir Bojonegoro, and (2) knowledge of the merit and effectiveness of using the thematic learning materials in the Arabic language for students of the elementary school teacher education department of the Islamic Institute of Religion Attanwir Bojonegoro. The researcher uses this research method of Research and Development with the method of education design for - ADDIE (Analysis, design, Development, Implementation, and Evaluation). Data collection method for this research is: observation, interview, questionnaire, test, and documentary. The method of data analysis is qualitative descriptive analysis with modified degree symbol. The results of the research are: (1) the process of developing thematic learning materials in the Arabic language is used in the method of “ADDIE”, meaning: Analysis, Design, Development, Application, and Evaluation. Its result is the thematic learning materials in the Arabic language that is written on paper B-5 and consists of 185 pages that are divided into three chapters, which are: 1) Arabic language in primary school, 2) Arabic language at the university, and 3) texts on education and Islam, and Arabic language. This learning materials uses the "18" Arabic Typsetting font. This learning materials is written for candidate of elementary school teachers. (2) The result of the material expert's verification experience gets the value 63 at the "very good" level, and the design expert gets the value 83 at the "very good" level. The student evaluation result is rated 2432 at the "very good" level. As for the result of the effective trial, it indicates that the promotion from the modified result in the pretest that attained the value 69.4% at the "acceptable" level, was upgraded to the value 77.1% at the "good" level. Therefore, the use of thematic learning materials in the Arabic language for students of the elementary school teacher education department of the Islamic Institute of Religion Attanwir Bojonegoro is "deserving" and "effective" in learning.